Grass gardens of the great plains region. - their care, and some important constituents. - Oakley, Russel Arthur (My University, 1903)
Introduction: For years botanists have been trying to determine the cause of prairies or grasslands, and as a result many theories have been advanced which, taken collectively, explain the existence of such areas in a large number of cases. As yet, however, no adequate theory or set of theories has been given that solves the problem for a portion of the Great Plains region. Perhaps the so called "wind" theory comes nearer filling the conditions than any other one alone. The greatest grassland in the world is in North America and includes the Great Plains. This area may be said to be a typical grassland area since it occupies the interior of the continent, and also because it is free from forests except in edaphic situations. The whole region seems to be, to a greater or less extent, an expression of the climate. Since the region mentioned is a grassland region, it seems natural that attention should be turned, in a more or less experimental way, to the culture and breeding of grasses. Recognizing the importance of this, the Experiment Stations of the Great Plains have established gardens or experimental fields for the purpose of testing the economic value of grasses; and also for the purpose of breeding up grasses that will become adapted to our climatic conditions. It is the purpose of this paper, to discuss such gardens and some important constituents in as much detail as space will permit. The Experiment Stations of this region are yet in their youth and as a consequence not every line or branch of experimentation is conducted in the very best manner possible. The grass garden is a very noticable example of this. There are other reasons too why grass gardens of this region are not as they should be; one is that heretofore they have not been considered of prime importance, the breeding of wheat and other cereals having received the greater attention. Another is that only recently has the region had to deal, to any great extent with worn out pastures. When the rent of pasture land suddenly leaped to four dollars per head per season, stockmen and farmers were confronted with the fact that they must either renovate their old pastures, seed new ones, or cut down the number of stock per acre. The reasons given help to explain the conditions of the grass gardens in the Experiment Stations today.
Citation: Oakley, Russel Arthur. Grass gardens of the great plains region. - their care, and some important constituents.. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Grasslands; Grasses; Irrigation; Records; Weeding and Cultivating; Chemical Analyses; Theses